Estratégias de cultivo utilizando resíduos das indústrias processadoras de alimentos e óleo de soja para produção de Poli (3-Hidroxibutirato) - Zortéa, Manoela Estefânea Boff (2012)
The diversity of use of polymeric materials causes concern because the use of non-renewable source for its production, as well as the environmental problems caused by the accumulation of the volume of solid waste generated. Seeking to minimize this problem were sought alternative products similar to plastics of petrochemical origin, one of them is the biodegradable polymer. The polyhydroxyalkanoates (PHAs) are polyesters synthesized by microorganisms from natural substances such as carbon and energy reserves, and accumulated by microbial cell in the form of intracellular granules, which may represent up to 80 % of the dry cell. The most studied polymer of this class is the polyhydroxybutyrate (P(3HB)) a biodegradable polymer that has similar features to the plastics from petroleum. This study aimed to develop for growth of bacteria Cupriavidus necator for the production of poly (3-hydroxybutyrate) using medium supplemented with cassava bagasse, whey and soybean oil. The first crops were carried out using a 2³ factorial design, to obtain the best condition at this stage of growth with the supplements tested. Other experiments used medium limited in nitrogen and higher amounts of supplements. The results obtained from the experimental design showed that the highest biomass production during growth was obtained in experiments which showed through the three supplements in their central levels, followed by testing supplements containing cheese whey and soybean oil combined or the presence of only one of these two components. Four experiments with increasing concentrations of supplement showed that waste and cheese whey hydrolyzed starch presented as good culture media for growth of C. necator, and the increased production of cell biomass (5,8 g.L-1) at the time of the nutrient nitrogen limitation occurred in the culture containing 100 % hydrolyzed starch conversion factor and the best substrate was obtained in cells in medium containing the highest amount supplement cheese whey (50 %).